Urban Agriculture in West Africa: Contributing to Food Security and Urban Sanitation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
These bi-lingual proceedings of a workshop organised in Ouagadougou, Burkina Faso, from 15 to 18 June 1998, include reports of the working groups and papers on rural-urban interactions, food production, urban waste management, and...